Intercourse Against Biological Children An Analysis of Islamic Law - Asman, Asman (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
Parental intercourse with biological children is in the spotlight among practitioners of Islamic law. Sexual intercourse against biological children is included in the category of adultery or sexual violence against children, because there are differences of opinion between practitioners of Islamic law regarding adultery and sexual violence against children. The aim of this research is to determine the perspective of Islamic law regarding sexual intercourse with biological children carried out by their parents (fathers). So the focus in this study is how is sexual intercourse against biological children from the perspective of Islamic law? The method in this study uses a type of descriptive qualitative research and while the pastor uses a normative approach so that what is emphasized is the result of the analysis of Islamic law related to sexual intercourse with biological children. The result in this study is that sexual intercourse against biological children is an act that violates Islamic law so that perpetrators of sexual intercourse can be stoned and can be expelled from their halamam village or exiled to a farther place or in Indonesian law perpetrators of sexual intercourse against biological children can be punished with a maximum prison sentence of 15 years in prison Persetubuhan orangtua terhadap anak kandung menjadi sorotan di kalangan praktisi hukum Islam. Persetubuhan terhadap anak kandung apakah termasuk kategori zina atau kekerasan seksual terhadap anak, karena ada perbedaan pendapat antara praktisi hukum Islam terkait perzinahan dan kekerasan seksual terhadap anak. Tujuan dalam penelitian ini adalah mengetahui sudut pandang hukum Islam terhadap persetubuhan terhadap anak kandung yang dilakukan oleh orang tuanya (bapak). Maka fokus dalam penelitian ini adalah bagaimana persetubuhan terhadap anak kandung perspektif hukum Islam? Metode dalam penelitian ini menggunakan jenis penelitian kualitatif deskriptif dan sedangkan pendekatanya menggunakan pendekatan normatif sehingga yang ditekankan adalah hasil dari analisis hukum Islam terkait persetubuhan terhadap anak kandung. Hasil dalam penelitian ini adalah persetubuhan terhadap anak kandung merupakan perbuatan yang melanggar syariat Islam